BENEFICIAL ROLE OF LASER COMBINED WITH INDIRECT SWIM UP SPERM PREPARATION IN INFERTILE MEN - Noor M. Kamel; Hussain Kh. Kadhem; Hayder A.L. Mossa; Bushra R. AL-Azzawi (Scholar Express Journals, 2022)
A laser is a perfect therapeutic option utilized in a variety of medical fields, including reproduction for better spermatozoa preparation and activation for improving spermatozoa activity and motility, and with the indirect swim-up procedure to reduce any round cells and leukocytes from the sample
Keywords: procedure; motility; spermatozoa